Structural and optical properties of Ba(Co1−xZnx)SiO4 (x = 0.2, 0.4, 0.6, 0.8). Issue 3 (September 2019) - Anike, J.; Derbeshi, R.; Wong-Ng, W.; Liu, W.; Windover, D.; King, N.; Wang, S.; Kaduk, J. A.; Lan, Y.
Abstract : Structural characterization and X-ray reference powder pattern determination have been conducted for the Co- and Zn-containing tridymite derivatives Ba(Co1−x Znx )SiO4 ( x = 0.2, 0.4, 0.6, 0.8). The bright blue series of Ba(Co1−x Znx )SiO4 crystallized in the hexagonal P6 3 space group (No. 173), with Z = 6. While the lattice parameter " a" decreases from 9.126 (2) Å to 9.10374(6) Å from x = 0.2 to 0.8, the lattice parameter " c" increases from 8.69477(12) Å to 8.72200(10) Å, respectively. Apparently, despite the similarity of ionic sizes of Zn 2+ and Co 2+, these opposing trends are due to the framework tetrahedral tilting of (ZnCo)O4 . The lattice volume, V, remains comparable between 626.27 Å 3 and 626.017 (7) Å 3 from x = 0 to x = 0.8. UV-visible absorption spectrum measurements indicate the band gap of these two materials to be ≈3.3 and ≈3.5 eV, respectively, therefore potential UV photocatalytic materials. Reference powder X-ray diffraction patterns of these compounds have been submitted to be included in the Powder Diffraction File (PDF).